LIVING THE LAUGHSCREAM: Human Technology and Affective Maneuvers in the Iraq War. (February 2017) - STONE, NOMI
ABSTRACT: In a new contribution to contemporary scholarship on war, I explore the epistemological and affective labors outsourced to individuals I call human technologies : populations of local wartime intermediaries and cultural role‐players employed by the U.S. military as embodied repositories of Middle East knowledge. Drawing on field‐work across the United States, this study focuses on the largely unexamined ethnographic spaces of U.S. military predeployment simulations in mock Middle Eastern villages. I focus on Iraqis who first worked for the U.S. military in Iraq as interpreters and then as role‐players within predeployment simulations in the United States. Through a close examination of the wartime labors of these individuals, this study illuminates how the intrinsic contradiction in the term human technology —the turning of person into machine for a singular use, foreclosing other forms of being and becoming—plays out on the ground. I demonstrate how the ironic disjuncture between military prescriptions for authenticity and role‐players' experiences of inauthenticity generates moments of affective rupture for those hired to embody their cultures. I argue that a charged tension manifests itself in the training apparatus: on an epistemological level, even as they experience excess, role‐players work to make the simulations "look good" to retain their jobs. Meanwhile, that excess manifests itself in affective overflow—in particular, one form that a role‐player called "the laughscream." I contend that such moments of affective excess create a momentary reprieve for role‐players, while typically not disturbing the military structure. The role‐players' laughter existentially negates the possibility that human beings can be tools, while permitting them, in practice, to be used as tools.